Administrative perspective on the forms of internal mobility, Case: Outokumpu Technology - Syrjäkari, Salla (My University, 2006)
Academic research on employee mobility concentrates strongly on expatriate assignments. However, when business becomes more global, mobility increases and new forms of employee mobility appear. Today, companies send assignees abroad in various ways. Also, advanced technology offers new ways of conducting business. This study concentrates on examining the forms of internal mobility. More specifically it will define the characteristics, advantages and disadvantages of project, commuter, virtual and development assignments. Secondly, it will look at these forms of non-standard international assignments in the context of HR processes. Finally, it will look at the future challenges of managing internal mobility. The chosen research method was a single case study that suits very well when the topic area is fresh and rather unknown. The study uses semi-structured interview as a main research tool. Hence, data is also collected from informal conversational interviews and the case company documents. The chosen method resulted into important academic and practical remarks. The study concludes that project assignment can appear in many forms. The length of an assignment is limited but can vary from days to years. The complexity of administration is dependent on the duration. Secondly, commuter assignment appears to be very demanding for the assignee. It should have limited duration but is often not recognized by HR due to line management control. Virtual assignment is difficult to perceive as a form of mobility due to physical stability. Therefore, the administration and management is also simpler. Finally, development assignment also presents itself in many forms. Processes and practices, their existence or non-existence, is dependent on the form of development assignment. Although companies have made attempts to develop their policies and practices concerning all non-standard international assignments, they still today remain rather undeveloped. However, they are now recognized and taken into consideration in HRM.
Keywords: Internal mobility; Project assignment; Commuter assignment; Virtual assignment; Development assignment; HR processes; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|